Sikap Masyarakat Surabaya Terhadap Iklan Televisi - Susanto, Hendro (Jurnal Widya Manajemen & Akuntansi, 2004)
Private television has taken a role in the fast growing of advertising media in Indonesia. All programs in the television such as entertainment news, movies,quizzes, etc. are inseparable with television advertising. This study was conducted lo learn public attitude to television advertising. The results showed that male respondent tend to pay more attention to television afuertising thanfemaler espondentT. hiss tudya lsofound that non studentr espondente ndt o pay morcittmtion to television advertising than student respondent.